Keraton Yogyakarta Cultural Diplomacy: Krida Mardawa as an Actor of Javanese Cultural Diplomacy in Introducing Cultural Heritage Value - Nugraha, Tian Adhia; Putri, Andini Hayu Agus; Ahmad, Mohammad Zaki (Journal of Paradiplomacy and City Networks, 2022)
Cultural diplomacy can be a way to strengthen state relations with the international community. Indonesia through the Keraton Yogyakarta has taken this method as an approach to enhance and establish ties with the destination country for cultural diplomacy. The Keraton Yogyakarta is known as an institution that maintains and preserves the Javanese culture of Yogyakarta. On several occasions, the Keraton Yogyakarta through Krida Mardawa. became an actor in Indonesian cultural diplomacy. This study shows the efforts made by the Keraton Yogyakarta through the arts division of Krida Mardawa in cultural diplomacy as well as promoting Indonesian culture abroad. This study uses qualitative data collection with primary sources and uses the approach of Cultural Diplomacy and Cultural Heritage Value theories, along with the concept of Cultural Institutions. In this study, there are findings that the Keraton Yogyakarta does not only carry out cultural diplomacy by promoting Javanese culture. but there are efforts to introduce the philosophical values possessed by Javanese culture to the international world.